RESTORATIVE JUSTICE DAN PROSPEK KEBIJAKAN IDEALNYA DALAM HUKUM PIDANA INDONESIA - Tongat Tongat (Masalah-Masalah Hukum, 2013)
Crime prevention through the means of criminal law with the conventional characteristics expensive, unjust, immoral and failure continues to be a central issue of criminal law. Criminal law is also constantly criticized for its negative impacts such as stigmatization, dehumanization and prisonization which tend to be crimi:10genic. State's failure to meet "promise" to protect citizens from crime continues to be a global issue roll away. The central role of the state, monopolistic in the crime prevention is also constantly harassed. State "required" divide the role in the prevention of crime proportionally with the community. Restorative justice which carries the '!balance of role idea in the prevention of crime be interesting issue that deserves appreciate academically.